2022
DOI: 10.1002/hipo.23486
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional regulation by “star forces”: Ionotropic astrocyte's optical stimulation suppresses synaptic plasticity, metabotropic one strikes back

Abstract: The role of astrocytes in modulating synaptic plasticity is an important question that until recently was not addressed due to limitations of previously existing technology.In the present study, we took an advantage of optogenetics to specifically activate astrocytes in hippocampal slices in order to study effects on synaptic function. Using the AAV-based delivery strategy, we expressed the ionotropic channelrhodopsin-2 (ChR2) or the metabotropic Gq-coupled Opto-a1AR opsins specifically in hippocampal astrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 74 publications
1
13
0
1
Order By: Relevance
“…Astrocytic activity induced LTP in the mouse hippocampus which contributes to learning and memory recall (Adamsky et al, 2018 ). On the murine hippocampus, optogenetic astrocyte activation elicited LTD alone via ChR2 and it elicited LTP via Opto‐a1AR (Maltsev et al, 2023 ). In the mouse striatum, astrocytic activation and adenosin release elicits LTD by solely astrocytic activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Astrocytic activity induced LTP in the mouse hippocampus which contributes to learning and memory recall (Adamsky et al, 2018 ). On the murine hippocampus, optogenetic astrocyte activation elicited LTD alone via ChR2 and it elicited LTP via Opto‐a1AR (Maltsev et al, 2023 ). In the mouse striatum, astrocytic activation and adenosin release elicits LTD by solely astrocytic activation.…”
Section: Discussionmentioning
confidence: 99%
“…On the murine hippocampus, optogenetic astrocyte activation elicited LTD alone via ChR2 and it elicited LTP via Opto-a1AR (Maltsev et al, 2023). In the mouse striatum, astrocytic activation and adenosin release elicits LTD by solely astrocytic activation.…”
Section: Sics Alone Are Capable Of Changing Synaptic Strengthmentioning
confidence: 97%
“…Previously, we determined that the stimulation of astrocytes expressing the OptoGq metabotropic construct led to an increase in the number of spontaneous excitatory postsynaptic currents (sEPSC) in the pyramidal neurons of the hippocampus, as well as to the potentiation of the fEPSP values in the acute brain slices of the hippocampus [ 5 ]. Moreover, the activation of Gq-coupled receptors in astrocytes enhanced early immediate gene expression [ 36 ]. Based on this evidence, the current study showed the effect of optogenetic stimulation of the metabotropic opsin OPTO-α1AR expressed in astrocytes on the formation of long-term potentiation in mice with the genetic model of Alzheimer’s disease known as 5xFAD.…”
Section: Discussionmentioning
confidence: 99%
“…One of the ways of precisely controlling or modulating astrocyte activity is the optogenetic method [5,[34][35][36]. This allows scientists to regulate the activity of different cells through genetically constructed photosensitive channels-opsins [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation